"Bibliological Magazine" - the ﬁrst professional magazine for librarians (Confluenţe Bibliologice, 2015)
The article deals with „Bibliological Magazine”, which is edited by the National Library of Moldova for 25 years. Alexe Rau, writer and philosopher, late bibliologist, was the chief-editor of the ﬁrst national specialized magazine in which the library values are promoted by authors from the country and abroad.In the magazine was introdused a heading oﬀered space for institutions at a certain age. This is occasioned the publication of number 3-4 of 2005 devoted to 60th anniversary of the Scientiﬁc Library of Alecu Russo Balti State University. Foreword article „The North Eeﬀect on the Library Science” was signed by Alexe Rau, „Balti University Library and its People” was written by Elena Harconita. The library has been congratulated by Nicolae Filip, Rector, Radu Motoc , the engineer, Honorary Member of the USARB Senate, Ion Madan,Professor, Iurie Colesnic, researcher and writer, Alexandru Budișteanu, dr.- architect, Doctor Honoris Causa of USARB, dr. Thomas Wilhelmi from Switzerland .
Keywords: library staff; Bibliological Magazine